REAKTUALISASI NILAI FARDU KIFAYAH MELALUI PENDEKATAN DAKWAH TRANSFORMASIONAL DI MASYARAKAT MUSLIM KONTEMPORER - Nurlia Hamdayani Munthe Munthe; Shohiba Pardede Pardede; Mujib Hagabean Nasution Nasution (Yayasan Baitul Hikmah al-Zain, 2026)
This research aims to comprehensively examine the relationship between da’wah and fardhu kifayah in Islam, as well as to identify the central role of da’wah in revitalizing the values of these collective obligations in the lives of individuals and society. The study uses a qualitative method with a library research approach, which involves in-depth analysis of authoritative sources such as the Qur’an, Hadith, fiqh books, and writings of classical and modern scholars .The results of the discussion show that da’wah is a broad concept that not only functions as a means of spreading Islamic teachings but also as a spiritual guide, character builder, driver of social change, balancer of injustice, unifier of community solidarity, and promoter of civilization. Meanwhile, fardhu kifayah is a collective obligation based on the principles of mutual cooperation and public interest (maslahah), which includes not only religious worship but also social, economic, and cultural issues. The role of da’wah in revitalizing the values of fardhu kifayah is realized through the dissemination of knowledge, the development of social awareness, the formation of an active attitude, the organization of networks and institutions, monitoring and evaluation, and the use of modern technology. Without da’wah, the values of fardhu kifayah tend to remain merely theoretical, while with effective da’wah, these values can come alive as culture and behavior, enabling the Muslim community to fulfill its role as a middle community (ummatan wasatan) that brings truth and goodness.